2016
DOI: 10.1590/abd1806-4841.20164016
|View full text |Cite
|
Sign up to set email alerts
|

Variants of CARD14 gene and psoriasis vulgaris in southern Chinese cohort

Abstract: BACKGROUND:Recent mutation analysis identified several missense mutations in CARD14 in psoriasis.OBJECTIVES:We performed the genomic sequence analysis on CARD14 in southern Chinese Han Cantonese with Psoriasis Vulgaris (PsV) to reveal more causative missense mutations.METHODS:A total of 131 patients with PsV and 207 matched controls were included. We conducted sequence analysis of all the exon and exon-intron boundaries of CARD14 in the group of PsV patients and subsequent case control analysis of potential se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In addition to the association of CARD14 variants with different disease entities, it is also noteworthy that several CARD14 variants have been associated with more than one type of skin disease. For example, p.D176H (Table 1 ), which was initially described in patients with PsV only ( 10 , 51 ) or PsV with PPP ( 41 , 76 ), was subsequently also described as associated with GPP but not with PsV in Asian populations ( 38 , 44 ) and Takeichi et al also found the p.D176H variant in patients with PRP type V ( 56 ). This reflects the broad heterogeneity found in patients with CARD14 mutations.…”
Section: Genetic Heterogeneity Associated With Card14 Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the association of CARD14 variants with different disease entities, it is also noteworthy that several CARD14 variants have been associated with more than one type of skin disease. For example, p.D176H (Table 1 ), which was initially described in patients with PsV only ( 10 , 51 ) or PsV with PPP ( 41 , 76 ), was subsequently also described as associated with GPP but not with PsV in Asian populations ( 38 , 44 ) and Takeichi et al also found the p.D176H variant in patients with PRP type V ( 56 ). This reflects the broad heterogeneity found in patients with CARD14 mutations.…”
Section: Genetic Heterogeneity Associated With Card14 Variantsmentioning
confidence: 99%
“…Following these initial studies, CARD14 variants were reported by several groups as causal or predisposing factors for psoriasis with or without psoriatic arthritis or palmoplantar pustular psoriasis (PPP) ( 36 51 ). Together, these studies indicate a diverse range of disease symptoms associated with CARD14 mutations.…”
Section: Inflammatory Skin Disorders Associated With Card14 Variantsmentioning
confidence: 99%
“…Since then, several studies have reported associations of CARD14 variants with psoriasis vulgaris, psoriatic arthritis, generalized pustular psoriasis, and palmoplantar pustular psoriasis (Ammar et al, 2013(Ammar et al, , 2016Eskin-Schwartz et al, 2016;Feng et al, 2016;Gonzalez-Lara et al, 2013;Inoue et al, 2016;Korber et al, 2013;Mossner et al, 2015;Qin et al, 2014;Sugiura et al, 2014Sugiura et al, , 2015Zhu et al, 2016). Furthermore, CARD14 variants have also been associated with pityriasis rubra pilaris, a distinct inflammatory skin disease characterized by keratotic follicular papules and salmon-colored erythematous plaques (Eytan et al, 2014;Fuchs-Telem et al, 2012;Has et al, 2016;Inoue et al, 2016;Li et al, 2015).…”
Section: Card14 Variants In Psoriasismentioning
confidence: 99%
“…Dectin-1, like other immune receptors (e.g., T cell receptor, B cell receptor, and NKG2D), employs immunoreceptor tyrosine-based activation motifs (ITAMs) to initiate downstream signaling via Src kinases (Thome, 2008). In T cells, Src kinase activity eventually leads to the activation of PKCq, which in turn phosphorylates and activates CARD11 (Jordan et al, 2012a;Mossner et al, 2015;Sugiura et al, 2014;Zhu et al, 2016) p.Arg179His 4 CC PsV/PPP 1.38 (Jordan et al, 2012a;Mossner et al, 2015) p.Val191Leu 4 CC PsV 1.02 (Jordan et al, 2012a) p.Glu197Lys 4 CC PPP/PsV/PsA 1.667 (Ammar et al, 2016;Mossner et al, 2015) p.Ser200Asn 4 CC PsV/GPP/PPP 0.67 (Ammar et al, 2016;Jordan et al, 2012a;Korber et al, 2013;Mossner et al, 2015) p.Leu209Pro 4 CC PsV 0.785 (Ammar et al, 2016) p.Ala216Thr 4 CC PsV 0.575 (Ammar et al, 2016;Qin et al, 2014;Zhu et al, 2016) p.Asp285Gly 6 None PsV 1.14 (Jordan et al, 2012a) p.Met338Val 7 CC PsV 0.914 (Ammar et al, 2016) p.Thr420Ala 9 none PsV 0.663 (Ammar et al, 2016) c.1356þ5G>A 9 CC PsV ND (Ammar et al, 2016) p.Thr591Met 13 PDZ PsV ND (Qin et al, 2014) p.Ile593 Asn 13 PDZ PsV 1.30 Jordan et al (2012a) p.Ser602Leu 13 PDZ PsV/GPP/PPP 1.196 (Ammar et al, 2016) p.Arg682Trp 15 SH3 PsV/GPP 0.95 (Jordan et al, 2012a;Qin et al, 2014) p.Gly714Ser 15 SH3 PsV 1.02 (Jordan et al, 2012a) p.Arg820Trp 18 GUK PsV/PsA ND (Feng et al, 2016;Gonzalez-Lara et al, 2013;Jordan et al, 2012a;Sugiura et al, 2015) p.Asp973Glu 21 GUK PsV ND (Jordan et al, 2012a) Details on the location of the mutations, their disease occurrence, and their effect on NF-kB activation is shown. The exon sequence was determined using transcript CARD14-201 (ENST00000344227 …”
Section: Card14-mediated Activation Of Paracaspase Malt1mentioning
confidence: 99%
“…While CARMA1 and CARMA3 play an essential role in NF-κB signaling induced by antigen receptors and certain G-protein-coupled receptors (GPCRs), respectively [ 1 , 2 ], in human keratinocytes CARMA2 plays an indispensable role in the signal transduction pathway that links pathogen-associated molecular pattern recognition to NF-κB activation [ 4 ]. Recent works have shown that mutations in CARMA2 segregate with several human inflammatory skin disorders, including familial and non-familial cases of psoriasis vulgaris, psoriatic arthritis, generalized pustular psoriasis, palmoplantar pustular psoriasis, and pityriasis rubra pilaris [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Many of the CARMA2 mutations associated with human skin disorders result in an increased activity of NF-κB transcription factor [ 2 , 4 , 5 , 19 ].…”
Section: Introductionmentioning
confidence: 99%